Open Knowledge Institutions: Reinventing Universities - Montgomery, Lucy; Hartley, John; Neylon, Cameron; Gillies, Malcolm; Gray, Eve; Herrmann-Pillath, Carsten; Huang, Karl; Leach, Joan; Potts, Jason; Ren, Xiang; Skinner, Katherine; Sugimoto, Cassidy; et al. (MIT Work in Progress, 2021)
In April 2018, thirteen of us from around Australia and the world gathered, with only the local kangaroos for company, in a secluded venue deep in the Moondyne Valley, an hour or so east of Perth, to think about the future of the university as an open knowledge institution. This book is the product of that thinking. It represents a consensus view from some distinct perspectives – research professors, open knowledge advocates, science communicators, economists, publishers, high-level university administrators, librarians and others – towards a diagnosis of what the problem is, and what we might do to fix it.